Brunners gland adenoma. Report of a case and literature review - Castillo Contreras, Ofelia (2009)
We report the case of a 69-year-old male patient with a large Brunners gland adenoma, who presented with symptomatic anemia and significant weight loss. The upper gastrointestinal endoscopy showed a large duodenal tumor extending form the bulb to the second portion, and the biopsy was reported as chronic non-specific duodenitis with gastric metaplastic changes. The patient underwent a duodenopancreatectomy, and the histological study of the surgical specimen was reported as a Brunners gland tumor. Brunners gland adenoma is considered a benign tumor of the duodenum; however, endoscopic resection is restricted to minor injuries.